Selection and application of China environmental sustainability policy instrumental: a quantitative analysis based on “Dual Carbon” policy text - Jing, Zhai; Feng, Hu (Frontiers in Environmental Science, 2024)
The "Dual Carbon" policy is a strategic instrument for the realization of the "Dual Carbon" target. The quantitative analysis of the "Dual Carbon" policy can provide theoretical support and decision-making reference for the institutional design and adjustment of the policy, so as to further improve the "Dual Carbon" 1+N policy system. By constructing a three-dimensional analysis framework of "instrument-goal-object", adopting the content analysis method, and combining the coding results of the "Dual Carbon" policy text to conduct multidimensional cross-analysis, we found that the overall design of the "Dual Carbon" policy is reasonable, but at the same time, there are problems such as unbalanced distribution of policy instruments, incomplete coverage of policy goals, insufficient synergy of policy objects, and low degree of matching between policy dimensions. In response to these problems, targeted mitigation measures are proposed.